Sulcus-Deepening Trochleoplasty as an Isolated or Combined Treatment Strategy for Patellar Instability and Trochlear Dysplasia: A Systematic Review - Michael Robert Davies, M.D; Sachin Allahabadi, M.D; Tarek Elliott Diab; Ryan David Freshman, M.D; Nirav Kiritkumar Pandya, M.D; Brian Thomas Feeley, M.D; Drew Anderson Lansdown, M.D (Elsevier, 2020)
Purpose: To highlight the indications and outcomes for sulcus-deepening trochleoplasty, when used as an isolated procedure as well as in combination with other stabilization techniques for patellar instability. Methods: We performed a systematic review focused on outcomes and complications following trochleoplasty performed either as an isolated procedure or in combination with other procedures to address patellar instability. Inclusion criteria included studies in English that reported on outcomes following primary open trochleoplasty, including Kujala scores and recurrent instability or dislocation events. Results: Twelve papers including 702 patients who underwent sulcus-deepening trochleoplasty were included. A total of 504 patients underwent isolated sulcus-deepening trochleoplasty, whereas 198 patients underwent trochleoplasty in combination with 1 or more additional stabilization procedures. In total, 67% of patients were female compared with 33% male. The procedure was done was a primary surgical intervention 74% of the time. Postoperative Kujala scores for isolated trochleoplasty ranged from 80 to 92, whereas those for combined stabilization procedures ranged from 76 to 95. The dislocation rate among the studies ranged from 0 to 8%. There was a persistent J-sign in 0 to 12% of treated knees among all studies, and a persistent apprehension test in 0 to 29% of treated knees. Return to play ranged from 65% to 83% in studies in which this was reported as an outcome. Conclusions: Sulcus-deepening trochleoplasty performed for recurrent patellar instability in the setting of trochlear dysplasia results in improved Kujala scores and a low redislocation rate, when performed as an isolated procedure or in combination with other stabilization procedures. Greater-level evidence is needed to better evaluate the overall efficacy of this procedure in addressing patellar instability. Level of Evidence: Level of Evidence, IV; Systematic review of level III and IV studies